+0  
 
0
51
1
avatar

I take variable $b$, double it, and add four. I subtract $4b$ from this new expression, and divide the resulting difference by two. What is my final expression in simplest form?

 Mar 5, 2020

Best Answer 

 #1
avatar+22043 
+2

b

2b + 4

2b + 4 -4b

(2b + 4 - 4b) / 2     =    (4 - 2b)/2 =  2 - b

 Mar 5, 2020
 #1
avatar+22043 
+2
Best Answer

b

2b + 4

2b + 4 -4b

(2b + 4 - 4b) / 2     =    (4 - 2b)/2 =  2 - b

ElectricPavlov Mar 5, 2020

34 Online Users

avatar
avatar
avatar
avatar
avatar
avatar
avatar